1994
DOI: 10.1677/jme.0.0120303
|View full text |Cite
|
Sign up to set email alerts
|

The oestrogen receptor modulates growth of pituitary tumour cells in the absence of exogenous oestrogen

Abstract: The GH3 pituitary cell line has been used to investigate the role of the oestrogen receptor (ER) as a modulator of mitogenic signals in tumour cells in the absence of exogenous oestrogen. Using a chemically defined, serum- and oestrogen-free medium, we have demonstrated that the pure steroidal anti-oestrogens ICI 182780 and ICI 164384 are capable of blocking growth by more than 50% after 5 days of culture. Studies with conditioned medium have indicated that the basal growth is due to the secretion of autocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This stimulation was blocked by an anti-oestrogen suggesting that IGF-1 was acting on a component of the ER pathway. In the absence of any E 2 , Newton et al (1994) also observed stimulation of ER-mediated reporter-gene activity by IGF-1 in the pituitary tumour cell line, GH 3 . The mechanism of this ligand-independent activation of the ER is still unclear but it may be involved in the development of tamoxifen resistance.…”
mentioning
confidence: 82%
“…This stimulation was blocked by an anti-oestrogen suggesting that IGF-1 was acting on a component of the ER pathway. In the absence of any E 2 , Newton et al (1994) also observed stimulation of ER-mediated reporter-gene activity by IGF-1 in the pituitary tumour cell line, GH 3 . The mechanism of this ligand-independent activation of the ER is still unclear but it may be involved in the development of tamoxifen resistance.…”
mentioning
confidence: 82%
“…Because vascular endothelial cells were not found to express the β-subunits of the channels [36], it is tempting to speculate that the BK Ca channel, where little or no β-subunits are co-expressed, is subject to inhibition by ICI-182,780. ICI-182,780 was also reported to suppress the growth of pituitary tumor cells and endothelial cells [35,37]. The BK Ca channel has been recently demonstrated to be presumably associated with growth control in human glioma cells [38].…”
Section: Ici-182780mentioning
confidence: 99%
“…An inhibition of protein kinase (PK) A, PKC and MAP kinase pathways also down-regulated IL-6induced reporter gene activity (Hobisch et al, 1998), however, inhibitors of PKC failed to block growth factor-dependent activation, suggesting multiple pathways for ligand-independent activation of ERα (Ignar-Trowbridge et al, 1996). Other examples of ligand-independent activation of ERα include IL-2 and insulinlike growth factor (IGF)-I (Newton et al, 1994a(Newton et al, , 1994b.…”
Section: mentioning
confidence: 99%
“…IL-6 is one such factor (Speirs et al, 1993;Duncan et al, 1994). There is evidence for cross-talk between ERα and growth factors with direct activation of ERα in response to IL-2 (Newton et al, 1994a) and IGF-I (Newton et al, 1994b;Lee et al, 1997) in ERα-positive breast and pituitary cell lines. Related to these observations, IL-6 has recently been shown to activate the androgen receptor in another hormone-sensitive cancer, prostate cancer (Hobisch et al, 1998).…”
mentioning
confidence: 99%